1964
DOI: 10.1002/j.1537-2197.1964.tb06654.x
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Absorption—an Active Uptake Process

Abstract: Mechanisms of foliar absorption of phosphate and rubidium in primary leaves of bean seedlings were resolved by a newly developed leaf‐immersion and leaf‐washing technique. Uptake was expressed as “specific absorption,” defined as mμmoles/cm2 leaf X 24 hr from a known concentration of substance in an external solution maintained in a known environment. Criteria for active uptake included time‐course analysis, temperature, oxygen, and energy dependence, sensitivity to metabolic inhibitors, accumulation against a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0
2

Year Published

1965
1965
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 22 publications
1
14
0
2
Order By: Relevance
“…Ricerche da lui condotte, mediante sostanze nutrienti marcate radioattivamente, hanno permesso, infatti, di ottenere risultati positivi in tal senso in piante colonizzate da endofiti. E' da tempo noto che i nutrienti fogliari, in misura diversa in base al tipo, possano penetrare attraverso la cuticola fogliare della pianta riducendo sintomi di carenza nutritiva (Antal & Joo 1995, Malakondaiah et al 1981, Bukovac & Wittwer 1957, Jyung & Wittwer 1964. Secondo Ragazzi (2004) nelle piante forestali, così come in quelle erbacee, il ruolo dominante degli endofiti sarebbe quello protettivo nei confronti di insetti, funghi e sostanze allelopatiche.…”
Section: Introduzioneunclassified
“…Ricerche da lui condotte, mediante sostanze nutrienti marcate radioattivamente, hanno permesso, infatti, di ottenere risultati positivi in tal senso in piante colonizzate da endofiti. E' da tempo noto che i nutrienti fogliari, in misura diversa in base al tipo, possano penetrare attraverso la cuticola fogliare della pianta riducendo sintomi di carenza nutritiva (Antal & Joo 1995, Malakondaiah et al 1981, Bukovac & Wittwer 1957, Jyung & Wittwer 1964. Secondo Ragazzi (2004) nelle piante forestali, così come in quelle erbacee, il ruolo dominante degli endofiti sarebbe quello protettivo nei confronti di insetti, funghi e sostanze allelopatiche.…”
Section: Introduzioneunclassified
“…However, it was first necessary to prepare leaf tissue in a form suitable for experimental use. The very slow rates of ion uptake found with immersed leaves (Jyung and Wittwer 1964) and isolated leaf cells (Jyung, Wittwer, and Bukovac 1965) suggested that these preparations were unsuitable. As a compromise, leaf disks and slices were studied and, in the course of this investigation, a similar evaluation was published by Smith and Epstein (1964).…”
Section: Introductionmentioning
confidence: 99%
“…The photosynthetic dependence of K+ uptake associated with growth was investigated by measuring the effect of DCMU, an inhibitor of PSII, on accumulation of K+ and uptake of 86Rb+ by leaf discs. The stimulation of K+ and Rb+ uptake by light has been observed in Nitella (28), Vallisneria (39), corn (Zea mays) (40), green bean (Phaseolus vulgaris) (19), pea (Pisum sativum) (34), and broad bean (Vicia faba) (18). Methods for studying ion uptake have included using whole cells, leaf slices and fragments, submerged leaves, and protoplasts.…”
mentioning
confidence: 99%